The 'Problem' of Girls' Education in Postcolonial Pakistan : A Study of Postcolonial Islamic Governmentalities in Rural Balochistan - Anwar, Javed, (Educational Research E-Books Online, Collection 2024., 2025)
The book charts a comprehensive account of girls' education in postcolonial Pakistan, and argues that the problem of girls' education in rural areas needs to be situated in the construction of knowledge, the practice of power relations, and the contested processes of truth production. Drawing on theories of Foucault's governmentality, postcolonialism and feminism, the author explores the context of Pakistan as a postcolonial Islamic nation-state, examines the British colonial legacies of governing institutions, discourses of gender and education, and development of girls' education policy and practices. The book contributes to the development of the analytical framework of postcolonial Islamic governmentality and uses the framework to analyse the research data, and education policy texts and discourses. See Less